A note on Mössbauer analysis of white oak surfaces colored with aqueous iron salt solutions. (1st March 2022) - Dagher, Roberta; Stevanovic, Tatjana; Ryan, Dominic H.; Landry, Véronic
Abstract: Aqueous solutions of iron salts can be applied to a wood surface to modify its color. When applied on wood, iron ions are chelated by the wood's natural phenolic compounds. The resulting color of the wood surface is due to the type of reaction products formed, such as mono-, bis- and tris- complexes of polyphenols with iron cations. In order to identify the different complexes formed on Quercus alba L. wood's surface and the oxidation state of iron after application of different iron salts on the same wood species which influence the resulting color of wood's surface, Mössbauer spectroscopy was performed directly on iron-stained wood samples. Colors of the stained wood samples, measured by a spectrophotometer, were analyzed in relation to the differences between the reaction products. The results showed that for a given wood species, the oxidation and reduction behavior of the iron depended on both the type of counterion and the oxidation state of the chosen iron salt.